Sensing of immature particles produced by dengue virus infected cells induces an antiviral response by plasmacytoid dendritic cells. - Elodie Décembre; Sonia Assil; Marine L B Hillaire; Wanwisa Dejnirattisai; Juthathip Mongkolsapaya; Gavin R Screaton; Andrew D Davidson; Marlène Dreux (PLoS Pathogens)
Dengue virus (DENV) is the leading cause of mosquito-borne viral illness and death in humans. Like many viruses, DENV has evolved potent mechanisms that abolish the antiviral response within infected cells. Nevertheless, several in vivo studies have demonstrated a key role of the innate immune response in controlling DENV infection and disease progression. Here, we report that sensing of DENV infected cells by plasmacytoid dendritic cells (pDCs) triggers a robust TLR7-dependent production of IFNα, concomitant with additional antiviral responses, including inflammatory cytokine secretion and pDC maturation. We demonstrate that unlike the efficient cell-free transmission of viral infectivity, pDC activation depends on cell-to-cell contact, a feature observed for various cell types and primary cells infected by DENV, as well as West Nile virus, another member of the Flavivirus genus. We show that the sensing of DENV infected cells by pDCs requires viral envelope protein-dependent secretion and transmission of viral RNA. Consistently with the cell-to-cell sensing-dependent pDC activation, we found that DENV structural components are clustered at the interface between pDCs and infected cells. The actin cytoskeleton is pivotal for both this clustering at the contacts and pDC activation, suggesting that this structural network likely contributes to the transmission of viral components to the pDCs. Due to an evolutionarily conserved suboptimal cleavage of the precursor membrane protein (prM), DENV infected cells release uncleaved prM containing-immature particles, which are deficient for membrane fusion function. We demonstrate that cells releasing immature particles trigger pDC IFN response more potently than cells producing fusion-competent mature virus. Altogether, our results imply that immature particles, as a carrier to endolysosome-localized TLR7 sensor, may contribute to regulate the progression of dengue disease by eliciting a strong innate response.